Exploring the role of autistic traits in treatment-resistant and clozapine-resistant schizophrenia: a comparative study - Başaran, Ahmet Selim; Türkel, Nur Nihal; Koparal, Buket; Kuruoğlu, Aslı (Frontiers in Psychiatry, 2025)
BackgroundTreatment resistance in schizophrenia is a major clinical challenge. While autistic traits are often more pronounced in patients with treatment-resistant schizophrenia (TRS), limited data exist on clozapine-resistant schizophrenia (CRS). This study aims to explore the relationship between autistic traits and treatment resistance in schizophrenia, with a focus on both TRS and CRS and to evaluate whether these traits could predict treatment outcomes.MethodsA total of 86 patients were included, divided into three groups: non-treatment-resistant schizophrenia (NRS, n=37), treatment-resistant schizophrenia (TRS, n=26), and clozapine-resistant schizophrenia (CRS, n=23). Psychopathology was assessed using the Positive and Negative Syndrome Scale (PANSS), while autistic traits were measured with the PANSS Autism Severity Scale (PAUSS) and the Autism Spectrum Quotient (AQ). Multinomial logistic regression models were used to determine the predictive value of autistic traits for TRS and CRS.ResultsStatistically significant differences were identified between the groups in PAUSS (p<0.001) and AQ (p<0.001) scores, indicating variations in autistic traits. PAUSS scores were predictive of TRS and CRS relative to NRS but did not differ between TRS and CRS. In contrast, AQ scores showed significant differences between TRS and CRS. Both PAUSS and AQ were negatively correlated with functionality as measured by the Global Assessment of Functioning, highlighting the impact of autistic traits on daily functioning.ConclusionsThe results indicate that autistic traits are associated with resistance to treatment, as PAUSS scores are predictive of the development of treatment-resistant and clozapine-resistant schizophrenia. However, the lack of statistically significant differences between TRS and CRS in PAUSS scores suggests that clozapine resistance may be influenced by additional factors beyond the autistic traits measured by PAUSS. To better understand the relationship between clozapine resistance and autistic traits, future research should not only focus on the autistic traits captured by PAUSS but also consider broader autism phenotypes or other distinct psychopathological processes. Such studies could offer deeper insights into the complex mechanisms that drive clozapine resistance and help identify new paths for treatment and intervention.